Cardiac Rehabilitation Enhancing Programs in Patients with Myocardial Infarction: A literature Review - Ahyana, Ahyana; Kritpracha, Charuwan; Thaniwattananon, Ploenpit (Nurse Media Journal of Nursing, 2013)
Background: Cardiac rehabilitation (CR) is a process that involves a multidisciplinary team of health professionals in order to optimize the status of patients’ physical, psychological, social, and vocational well being. The CR program has been proven to influence health outcomes in patients with cardiac diseases, particularly myocardial infarction (MI) and stable angina. However, patients’ compliance with cardiac rehabilitation programs remains a challenge.Purpose: The purpose of this study is to review and identify interventions that enhance cardiac rehabilitation behaviors in MI patients.Method: A literature review was conducted by analyzing related research reports published since 2000 to 2012. Only English language articles were included.Result: There were 10 experimental studies and 2 meta-analysis studies. Interventions widely used to enhance cardiac rehabilitation behaviors in MI patients were self-efficacy and self management derived programs. These programs involved interventions that enhance cardiac rehabilitation behaviors, including training exercise, behavioral change, education and psychological support, and lifestyle changing strategies. None have reported the use of culturally tailored intervention. Four phases of cardiac rehabilitation were accepted as each phase represents a different aspect of care: inpatient care, early post discharge period, exercise training, and long term follow up. Critical factors for patients in maintaining an optimum health condition after a cardiac event are, in order, status of patient’s physical, psychological, social, and vocational well being.Conclusion: Cardiac Rehabilitation program has been shown to improve quality of life and decrease mortality in MI patients. The development of culturally specific interventions to increase cardiac rehabilitation behaviors will provide a significant improvement for cardiac patient’s care that ultimately results in better health outcomes. Health care professionals should be involved in CR programs in order to enhance patients’ performance in CR behaviors; moreover, further study is also needed to examine the existing intervention studies to improve the CR program.Keywords: cardiac rehabilitation, attendance, behaviors, outcomes, secondary prevention and myocardial infarction (MI).